2004
DOI: 10.1128/jcm.42.7.3046-3051.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Mycobacterium tuberculosis in Western Sweden

Abstract: The genetic diversity of Mycobacterium tuberculosis isolates among patients from Sweden was determined by a combination of two PCR-based techniques (spoligotyping and variable number of tandem repeats analysis). It resulted in a clustering of 23.6% of the isolates and a rate of recent transmission of 14.1%. The clustered isolates mainly belonged to the Haarlem family (23.2%), followed by the Beijing (9.8%), Latin American and Mediterranean (LAM; 8%), and East African-Indian (EAI; 6.2%) families. A comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 33 publications
4
29
0
1
Order By: Relevance
“…This could reflect the likelihood of infection having occurred in the country of origin prior to entry to Italy or within particular ethnic communities in the host country. This is in agreement with the widely accepted hypothesis that in low-prevalence countries, foreign-born people are infected in their country of origin and then develop disease shortly after immigration (5,7,8,21). Similar observations of limited transmission from foreign-born patients to United States-born individuals have been reported from molecular cluster analyses in San Francisco (6,17) and, more recently, by Hirsh et al (16) using deletion analysis.…”
Section: Discussionsupporting
confidence: 78%
“…This could reflect the likelihood of infection having occurred in the country of origin prior to entry to Italy or within particular ethnic communities in the host country. This is in agreement with the widely accepted hypothesis that in low-prevalence countries, foreign-born people are infected in their country of origin and then develop disease shortly after immigration (5,7,8,21). Similar observations of limited transmission from foreign-born patients to United States-born individuals have been reported from molecular cluster analyses in San Francisco (6,17) and, more recently, by Hirsh et al (16) using deletion analysis.…”
Section: Discussionsupporting
confidence: 78%
“…This remarkable difference was also reflected by the rate of recent transmission that was as high as 49.3% in French Guiana, compared to 16.9% and 27.2% in Martinique and Guadeloupe, respectively. Thus, the rate of recent transmis- sion in FWI is relatively low, with values for Martinique being close to those reported in low-incidence areas like Sweden (14.1% [4]), and London, England (14.4% [17]), and those for Guadeloupe being similar to Denmark (24% [34]) and Paris, France (25% 15). On the contrary, the rate of recent transmission of TB in French Guiana with a value of around 50% is close to data reported from high-incidence areas like Equatorial Guinea (28), Zimbabwe (10), Cape Town, South Africa (31), and Antananarivo, Madagascar (19).…”
Section: Discussionmentioning
confidence: 69%
“…As explained in a previous study (4), all the isolates with the exception of true orphans in the database were attributed a clade designation based on minor and major visual rules for spoligotyping-based classification (12,22). As summarized in Tables 2 and 3, this permitted us to designate 11 clades: Africanum; Beijing; Bovis; Central Asia [CAS]; East-African Indian [EAI]; Haarlem, Latin-American, and Mediterranean [LAM]; Manu; S; X; and an ill-defined T clade.…”
Section: Resultsmentioning
confidence: 88%
“…Nevertheless, there are conflicting results in the literature on the relative transmissibility of drug-resistant and drug-sensitive M. tuberculosis strains. While some studies showed that drugresistant isolates were less likely to be associated with clustering (46,48), others identified drug resistance as a strong predictor of being in a cluster (1,10). In spite of a high degree of genetic diversity, an important part (41.3%), of the analyzed MDR strains belonged to one of the four clusters SIT53, SIT891, SIT1, and SIT1557.…”
mentioning
confidence: 99%